Edmund Husserl's Freiburg years, 1916-1938 - Mohanty, J. N. (Jitendra Nath), 1928- (Yale University Press, 2011)
In his award-winning book The Philosophy of Edmund Husserl: A Historical Development, J.N. Mohanty charted Husserl's philosophical development from the young man's earliest studies--informed by his work as a mathematician--to the publication of his Ideas in 1913. In this welcome new volume, the author takes up the final decades of Husserl's life, addressing the work of his Freiburg period, from 1916 until his death in 1938. As in his earlier work, Mohanty here offers close readings of Husserl's main texts accompanied by accurate summaries, informative commentaries, and original analyses. This book, along with its companion volume, completes the most up-to-date, well-informed, and comprehensive account ever written on Husserl's phenomenological philosophy and its development.